Perivascular epithelioid cell tumor of the uterus and pelvic cavity - Yu, Xiuzhang; Yang, Bowen; Huang, Liyan; Hou, Minmin; Qie, Mingrong (Frontiers in Oncology, 2024)
BackgroundPrimary perivascular epithelioid cell tumors (PEComas) of the female reproductive tract have been primarily reported as case reports owing to their clinical rarity. Limited incidence rates and clinical case data hinder a comprehensive understanding of the risks and invasiveness of this disease. We discuss herein the diagnosis, treatment, and prognosis of this disease to enhance comprehension and therapeutic strategies.MethodsWe conducted a clinical analysis of patients with PEComa treated at the Gynecology Department of The West China Second University Hospital of Sichuan University between May 2018 and January 2024. Diagnosis and treatment were evaluated based on pertinent literature.ResultsOverall, eight patients (seven patients with tumors in the uterus and one patient with tumors in the pelvic cavity) were evaluated. One patient with PEComa of unknown malignant potential and two patients with malignant PEComa underwent hysterectomy and bilateral adnexectomy with or without adjuvant therapy and did not develop recurrence. Meanwhile, three patients who underwent lesion resection only exhibited radiological evidence of new lesions. Furthermore, postoperative imaging identified new pulmonary nodules in three patients.ConclusionAlthough the current criteria are generally effective in assessing the tumor invasiveness of PEComa, emphasizing the significance of complete lesion resection remains crucial. Inadequate treatment significantly increases the risks of recurrence and metastasis. Additionally, the prevalence of pulmonary metastases may have been underestimated. Refining risk stratification to prevent overtreatment of low-grade malignancies or overlooking highly aggressive tumors is an important area for further study.